Analysis of MicroRNA Expression Changes During the Course of Therapy In Rectal Cancer Patients - Cervena, Klara; Novosadova, Vendula; Pardini, Barbara; Naccarati, Alessio; Opattova, Alena; Horak, Josef; Vodenkova, Sona; Buchler, Tomas; Skrobanek, Pavel; Levy, Miroslav; Vodicka, Pavel; Vymetalkova, Veronika (Frontiers in Oncology, 2021)
MicroRNAs (miRNAs) regulate gene expression in a tissue-specific manner. However, little is known about the miRNA expression changes induced by the therapy in rectal cancer (RC) patients. We evaluated miRNA expression levels before and after therapy and identified specific miRNA signatures reflecting disease course and treatment responses of RC patients. First, miRNA expression levels were assessed by next-generation sequencing in two plasma samplings (at the time of diagnosis and a year after) from 20 RC patients. MiR-122-5p and miR-142-5p were classified for subsequent validation in plasma and plasma extracellular vesicles (EVs) on an independent group of RC patients (n=107). Due to the intrinsic high differences in miRNA expression levels between samplings, cancer-free individuals (n=51) were included in the validation phase to determine the baseline expression levels of the selected miRNAs. Expression levels of these miRNA were significantly different between RC patients and controls (for all p <0.001). A year after diagnosis, miRNA expression profiles were significantly modified in patients responding to treatment and were no longer different from those measured in cancer-free individuals. On the other hand, patients not responding to therapy maintained low expression levels in their second sampling (miR-122-5p: plasma: p=0.05, EVs: p=0.007; miR-142-5p: plasma: p=0.008). Besides, overexpression of miR-122-5p and miR-142-5p in rectal cancer cell lines inhibited cell growth and survival. This study provides novel evidence that circulating miR-122-5p and miR-142-5p have a high potential for rectal cancer screening and early detection as well as for the assessment of patients’ outcomes and the effectiveness of treatment schedule.